Achievement of treatment goals for secondary prevention of myocardial infarction or stroke in 29, 325 patients with type 2 diabetes: a German/Austrian DPV-multicenter analysis. Issue 1 (December 2016) - Bohn, Barbara; Schöfl, Christof; Zimmer, Vincent; Hummel, Michael; Heise, Nikolai; Siegel, Erhard; Karges, Wolfram; Riedl, Michaela; Holl, Reinhard
Abstract Background To analyze whether medical care is in accordance with guidelines for secondary prevention of myocardial infarction (MI), or stroke in patients with type 2 diabetes from Germany and Austria. Methods 29, 325 patients (≥20 years of age) with type 2 diabetes and MI, or stroke, documented between 2006 and 2015 were selected from the Diabetes-Patienten-Verlaufsdokumentation database. We analyzed medication, clinical characteristics, and lifestyle factors according to national secondary prevention guidelines in patients with MI, or stroke, separately. Results HbA1C <7.5 % was achieved in 64.9 % (MI), and in 61.1 % (stroke) of patients. LDL <100 mg/dl was documented in 56.2 % (MI), and in 42.2 % (stroke). Non-smoking was reported in 92.0 % (MI), and in 93.1 % (stroke), physical activity in 9.6 % (MI), and 5.5 % (stroke). Target values of blood pressure (<130/80 mmHg in MI, 120/70–140/90 in stroke) were reached in 67.0 % (MI), and in 89.9 % (stroke). Prescription prevalence of inhibitors of platelet aggregation (IPA) was 50.7 % (MI), and 31.7 % (stroke). 57.0 % (MI), and 40.1 % (stroke) used statins, 65.1 % (MI), and 65.8 % (stroke) used any type of antihypertensives, and ACE inhibitors were prescribed in 49.7 % (MI), and 41.3 % (stroke). A body mass index (BMI) <27 kg/m2 and the use of beta blockers were only recommended in subjects with MI. Of the patients with MI, 32.0 % had a BMI <27 kg/m2, and 59.5 % used beta blockers. Conclusions Achievement of treatment goals in secondary prevention of MI, or stroke in subjects with type 2 diabetes needs improvement. Target goals were met more frequently in patients with MI compared to subjects with stroke. Especially the use of IPA was very low in patients with stroke. There remains great potential to reduce the risk of repeated macrovascular events and premature death, as well as to increase patients' quality of life.